Decentralized internet-of-things networks for environmental data pipelines: opportunities and challenges in a community-based urban green space restoration project in Nairobi, Kenya - Fiegenbaum, Hanna; Azegele, Bradley; Seider, Stephan (Frontiers in Blockchain, 2026)
Decentralized IoT-networks are part of a broader class of decentralized physical infrastructure networks (DePIN), which use blockchain to decentralize, incentivize, and reward the operation and maintenance of technical infrastructure. This study examines how decentralized IoT-networks can address challenges in the design and governance of environmental data streams and reduce adoption barriers for monitoring infrastructure. It draws on the deployment of IoT sensors for measuring environmental variables in a community-based urban restoration project in Nairobi, Kenya. The paper discusses technical features and presents observations on network reliability, reductions in operational costs, accessibility, and community participation. The findings suggest that decentralized IoT systems hold promise for enhancing distributed environmental data collection and transparent multi-party governance, due to significant reductions in operational costs, the potential for fractional income generation, traceable data trails, and inclusive governance mechanisms.